Eastern and western in Egyptian literature - Шихaлибейли З. Э. (Journal of Oriental Studies, 2017)
The arabic literature, which was in inertia for centuries, in XIX century has entered in to a new stage of development. One of the main indicators of this new era was the wide distribution of European influence in the Arab world. From the beginning of XIX century arabic literature, especially Egyptian literature, felt revival. Arabic literature gradually leave fetter of past and takes way to theories, literatures and life styles of Western Europe, makes strong relations with French literature. The fact that for over a century Arabs had been under direct influence of the Western European literature, culture and even lifestyle is the irrefutable evidence of how significant it was not only for Egyptian literary, but for the whole of Arabic literature in general.